Monitoring Aedes populations for arboviruses, Wolbachia, insecticide resistance and its mechanisms in various agroecosystems in Benin - Ateutchia-Ngouanet, S.; Nanfack-Minkeu, F.; Mavridis, K.; Wanji, S.; Demanou, M.; Vontas, J.; Djouaka, R. (Elsevier, 2024)
Aedes mosquitoes are the main vectors of arboviruses in Benin. Cases of dengue have been reported in Benin with all four serotypes of the virus actively circulating in this region. Some agricultural settings are known to harbor Aedes vectors responsible for the transmission of arboviruses. The massive use of certain insecticides in agricultural settings has probably contributed to insecticide resistance in these vectors. In Benin, the susceptibility of arbovirus vectors to insecticides is poorly studied. In addition, the distribution of Wolbachia spp., which is used against some arboviruses is unknown. Moreover, there is limited information regarding the vectors responsible for the transmission of arboviruses in Benin. This present study monitored the species composition, arboviruses, and Wolbachia symbiont status, as well as the phenotypic and molecular insecticide resistance profile of Aedes populations from three agroecosystems in Benin. Aedes species identification was performed morphologically and confirmed using qPCR. (RT)-qPCR assay was applied for monitoring the presence of DENV, CHIKV, ZIKV, and WNV pathogens as well as for naturally occurring Wolbachia symbionts. Insecticide resistance was assessed phenotypically, by permethrin (0.75%) exposure of Adults (F0) using World Health Organization (WHO) bioassay protocols, and at the molecular level, using TaqMan (RT)-qPCR assays for assessing knock-down resistance (kdr) mutations (F1534C, V1016G/I, and S989P) and the expression levels of eight detoxification genes (P450s from the CYP9 and CYP6 families, carboxylesterases and glutathione-S-transferases). Aedes aegypti (Ae. aegypti) mosquitoes were the most abundant (93.9%) in the three agroecosystems studied, followed by Aedes albopictus (Ae. albopictus) mosquitoes (6.1%). No arboviruses were detected in the study's mosquito populations. Naturally occurring Wolbachia symbionts were present in 7 pools out of 15 pools tested. This could influence the effectiveness of vector control strategies based on exogenously introduced Wolbachia, all present in the three agroecosystems. Full susceptibility to permethrin was observed in all tested populations of Ae. albopictus. On the contrary, Ae. aegypti were found to be resistant in all three agroecosystem sites except for banana plantation sites, where full susceptibility was observed. Molecular analysis revealed that individual target site resistance kdr mutations F1534C and V1016G/I were detected in most Ae. aegypti populations. Additionally, double mutant (F1534C + V1016G/I) mosquitoes were found in some populations, and in one case, triple mutant (F1534C + V1016G/I + S989P) mosquitoes were detected. Metabolic resistance, as reflected by overexpression of three P450 genes (CYP6BB2, CYP9J26, and CYP9J32), was also detected in Ae. aegypti mosquitoes. Our study provides information that could be used to strategize future vector control strategies and highlights the importance of continuing vector surveillance. Future studies should assess the effect of piperonyl butoxide (PBO) on metabolic resistance and identify the different strains of Wolbachia spp., to choose the best vector control strategies in Benin.